Wnt1 Inducible Signaling Pathway Protein 1 (WISP1) Blocks Neurodegeneration through Phosphoinositide 3 Kinase/Akt1 and Apoptotic Mitochondrial Signaling Involving Bad, Bax, Bim, and Bcl-xL - Wang, Shaohui; Zhong Chong, Zhao; Chen Shang, Yan; Maiese, Kenneth (Current Neurovascular Research, 2012)
Wnt1 inducible signaling pathway protein 1 (WISP1) is a member of the CCN family of proteins that determine cell growth, cell differentiation, immune system activation, and cell survival in tissues ranging from the cardiovascular-pulmonary system to the reproductive system. Yet, little is known of the role of WISP1 as a neuroprotective entity in the nervous system. Here we demonstrate that WISP1 is present in primary hippocampal neurons during oxidant stress with oxygen-glucose deprivation (OGD). WISP1 expression is significantly enhanced during OGD exposure by the cysteine-rich glycosylated protein Wnt1. Similar to the neuroprotective capabilities known for Wnt1 and its signaling pathways, WISP1 averts neuronal cell injury and apoptotic degeneration during oxidative stress exposure. WISP1 requires activation of phosphoinositide 3-kinase (PI 3-K) and Akt1 pathways to promote neuronal cell survival, since blockade of these pathways abrogates cellular protection. Furthermore, WISP1 through PI 3-K and Akt1 phosphorylates Bad and GSK-3β, minimizes expression of the Bim/Bax complex while increasing the expression of BclxL/ Bax complex, and prevents mitochondrial membrane permeability, cytochrome c release, and caspase 3 activation in the presence of oxidant stress. These studies provide novel considerations for the development of WISP1 as an effective and robust therapeutic target not only for neurodegenerative disorders, but also for disease entities throughout the body.
Keywords: cysteine